2017
DOI: 10.1108/bfj-08-2016-0354
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting the organic food market in Lebanon: an application of k-means cluster analysis

Abstract: Purpose: The purpose of this paper is to discover profiles of organic food consumers in Lebanon by performing a market segmentation based on lifestyle and attitude variables and thus be able to propose appropriate marketing strategies for each market segment. Design/methodology/approach: A survey, based on the use of closed-ended questionnaire, was addressed to 320 organic food consumers in the capital Beirut, in February and March 2014. Descriptive analysis, principal component analysis and cluster analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…The concept of nostalgic and similarity to baladi food reflects the perception of organic production as a traditional way of producing food. Other studies have found this association to be strong in the Lebanese consumers' perception of organic food (Pugliese, Zanasi, Atallah, & Cosimo, 2013;Tleis et al, 2017) and in other emerging markets as well. One study found that organic in Brazil and China is perceived as traditional and safe and that organic products are linked with familyfarms, and "natural" (pesticide-free) production (Thøgersen et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The concept of nostalgic and similarity to baladi food reflects the perception of organic production as a traditional way of producing food. Other studies have found this association to be strong in the Lebanese consumers' perception of organic food (Pugliese, Zanasi, Atallah, & Cosimo, 2013;Tleis et al, 2017) and in other emerging markets as well. One study found that organic in Brazil and China is perceived as traditional and safe and that organic products are linked with familyfarms, and "natural" (pesticide-free) production (Thøgersen et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that concern for nature is more imperative for organic food consumption in Lebanon than it appears from the HVMs. Concern for nature is commonly found to be coupled with organic food consumption in developed markets (Haas et al, ; Padel & Foster, ; Zagata & Lostak, ; Zanoli & Naspetti, ) but was not identified before as a key motivation in the Lebanese organic market (Tleis, Callieris, & Roma, ). Hence, this finding is the first indication of a relative prominence of the environmental considerations dimension in the food choices of an important and committed segment of organic food consumers, suggesting a possible direction for the emergence of the organic market in Lebanon.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that that demographic analysis did not provide the information needed for successful targeting of organic food consumers, many authors applied segmentation analysis in order to identify the characteristics of different segments of organic food consumers. The results revealed that the same segments of organic food consumers cannot be found in all investigated markets, i.e., that organic food consumers have different demographic, psychographic, and behavioral characteristics, observed in different markets and different countries [9,20,25,26]. Therefore, different studies were conducted regarding consumer perception and barriers that prevent them from buying these products in order to better understand what drives the consumption of organic products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since consumers are highly variable, hierarchical cluster analysis – a long‐established method – can be used to differentiate human behaviour and identify consumer preference . It has been used in multiple food sectors such as genetically modified food, organic food and low‐fat salami . This approach has been combined with external preference mapping to identify the sensory attributes that impact cheddar cheese acceptability among cluster groups .…”
Section: Literature On the Differences In Consumer Liking Of Beefmentioning
confidence: 99%